Continuing Difficulties in English Teachers' Preparation for Cambridge Exams - Rosarina Poppy Handayani; Endah Yulia Rahayu; Nukmatus Syahria; Nico Irawan; Komm Pechinthorn (Academia Open, 2025)
Standardized teacher assessments such as the Cambridge Teaching Knowledge Test (TKT) are increasingly used to evaluate pedagogical knowledge, yet their integration into local educational settings remains challenging. Specifically in Indonesia, elementary English as a Foreign Language (EFL) teachers face unique barriers during TKT preparation due to contextual misalignment. Despite existing studies on teacher training and assessment, limited research addresses the lived experiences of teachers navigating TKT preparation in resource-constrained environments. This study aims to explore the perceptions, challenges, and outcomes encountered by eight Indonesian EFL teachers during a six-session TKT preparation program using a narrative inquiry approach. Findings reveal minimal improvement in test readiness, largely influenced by limited preparation time, insufficient training resources, and incongruity between TKT content and local teaching realities. The novelty lies in its focus on narrative insights from in-service primary school teachers, often underrepresented in assessment literature. Implications suggest that for standardized assessments like the TKT to be effective and equitable, localized training support, contextual adaptation, and sustained mentoring are essential. This study contributes to the discourse on EFL teacher development by exposing the practical dissonance between global certification frameworks and local instructional ecosystems. Highlights: Highlights contextual barriers faced by Indonesian EFL teachers during TKT prep. Reveals misalignment between global tests and local teaching practices. Emphasizes need for localized support in standardized teacher training. Keywords: Narrative Study, Cambridge TKT Preparation, Teacher Training Challenges, EFL Test Readiness, Standardized Teacher Assessment